# A is as much younger than B as he is older than C. If thd sum of the ages of B and C is 48years. What is the present age of A?

2
Log in to add a comment

Log in to add a comment

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

A is younger than B

and A is older than C

A/q

(age of A) - (age of C) = (age of B) - (age of A)

⇒2A = B +C

and B+C = 48______(given)

so, 2A = 48

**age of A = 24 years**

and A is older than C

A/q

(age of A) - (age of C) = (age of B) - (age of A)

⇒2A = B +C

and B+C = 48______(given)

so, 2A = 48

Certified answers contain reliable, trustworthy information vouched for by a hand-picked team of experts. Brainly has millions of high quality answers, all of them carefully moderated by our most trusted community members, but certified answers are the finest of the finest.

Given A is younger than B as he is elder than C.

Let the difference between the age of A and B and A and C which is equal be 'y'.

Now,A=B-y

and A=C+y

Now A=B-y

therefore,y=B-A,which is the L.H.S

Now A=C+y

Therefore ,y=A-C,which is the R.H.S

Now,L.H.S-R.H.S

ie;y-y=(B-A)-(A-C)

0=B-A-A+C

0=B+C-A-A

0=48-2A

ie;48=2A

Therefore A=48/2

=24.

Let the difference between the age of A and B and A and C which is equal be 'y'.

Now,A=B-y

and A=C+y

Now A=B-y

therefore,y=B-A,which is the L.H.S

Now A=C+y

Therefore ,y=A-C,which is the R.H.S

Now,L.H.S-R.H.S

ie;y-y=(B-A)-(A-C)

0=B-A-A+C

0=B+C-A-A

0=48-2A

ie;48=2A

Therefore A=48/2

=24.